Libertad, religión y laicidad en materia electoral: ponderaciones comparadas - Contipelli, Ernani (Revista de Derecho, 2019)
This article aims to present the influence of the value of freedom in defining of the secular state, establishing its relationship with the political-electoral rights. From this perspective of view, we intend to discuss religious freedom and its mutation process in line with the equality and dignity of the hum an person, to verify its correspondence with reality of the social-axiology. And, finally, to establish a comparison of the Brazilian constitutional practice regarding state secularism and religious freedom with the constitutional provisions contained in the Mexican legal system.